A clinical and radiological profile of short stature in Central India - Agrawal, Nidhi; Barua, Devendra; Bhandari, Pranay (International Journal of Contemporary Pediatrics, 2023)
Background: Stature is methodically described as height vertex. Short stature can be defined as an individual in whom height is two standard deviations below the standard mean height of a given sex, age and population. Methods: A cross sectional study was conducted in 200 children attending endocrine OPD over 12 months from October 2019 to September 2020 with complaints of short stature to study the clinical and radiological profile of children between 2-15 years of age. Results: Totally 200 children with short stature were studied in age group less than 15 years. Total no. of males were 105 (52.5%) and females were 95 (47.5%). The highest percentage of patients i.e., 38.5% belonged to 5-10 years followed by 36% who were of 10-15 years of age group while, the least i.e., only 25.5% belonged to <5 years of age group. Conclusions: In our study endocrine causes are most common including hypothyroid (27.5%), GHD (2.5%) and adrenal insufficiency (1%). 2nd most common are normal variants CDGP (11.5%) and FSS (9%). After endocrine causes this dominance of normal variants of growth is in accordance with other worldwide studies. Thus, it is very important to remember that many cases of short stature in general population may be normal, as determined by meticulous measurements, and determination of bone age using standard charts and expert’s radiological opinion.